Depersonalised doctors: a cross-sectional study of 564 doctors, 760 consultations and 1876 patient reports in UK general practice. Issue 1 (2nd February 2012) - Orton, Peter; Orton, Christopher; Pereira Gray, Denis
Abstract : Objectives: The objectives of this study were to assess burnout in a sample of general practitioners (GPs), to determine factors associated with depersonalisation and to investigate its impact on doctors' consultations with patients. Design: Cross-sectional, postal survey of GPs using the Maslach Burnout Inventory (MBI). Patient survey and tape-recording of consultations for a subsample of respondents stratified by their MBI scores, gender and duration of General Medical Council registration. Setting: UK general practice. Participants: GPs within NHS Essex. Primary and secondary outcome measures: Scores on MBI subscales (depersonalisation, emotional exhaustion, personal accomplishment); scores on Doctors' Interpersonal Skills Questionnaire and patient-centredness scores attributed to tape-recorded consultations by independent observers. Results: In the postal survey, 564/789 (71%) GPs completed the MBI. High levels of emotional exhaustion (261/564 doctors, 46%) and depersonalisation (237 doctors, 42%) and low levels of personal accomplishment (190 doctors, 34%) were reported. Depersonalisation scores were related to characteristics of the doctor and the practice. Male doctors reported significantly higher (p<0.001) depersonalisation than female doctors. Doctors registered with the General Medical Council under 20 years had significantly higher (p=0.005) depersonalisation scores than those registered for longer. Doctors in group practices had significantly higher (p=0.001) depersonalisation scores than single-handed practitioners. Thirty-eight doctors agreed to complete the patient survey (n=1876 patients) and audio-record consultations (n=760 consultations). Depersonalised doctors were significantly more likely (p=0.03) to consult with patients who reported seeing their 'usual doctor'. There were no significant associations between doctors' depersonalisation and their patient-rated interpersonal skills or observed patient-centredness. Conclusions: This is the largest number of doctors completing the MBI with the highest levels of depersonalisation reported. Despite experiencing substantial depersonalisation, doctors' feelings of burnout were not detected by patients or independent observers. Such levels of burnout are, however, worrying and imply a need for action by doctors themselves, their medical colleagues, professional bodies, healthcare organisations and the Department of Health.